2010
DOI: 10.1007/s11999-009-1083-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ‘Squeaking’ After Ceramic-on-Ceramic Total Hip Arthroplasty

Abstract: The incidence of hip ''squeak'' associated with ceramic-on-ceramic bearings has been variably reported, ranging from 0.7% to 20.9%. We determined the patients' perception of squeaking in 306 patients (336 hips) in whom ceramic-on-ceramic total hip arthroplasties (THAs) were performed between 1997 and 2005. A questionnaire regarding hip noise was obtained by telephone. With a minimum followup of 2 years (mean, 3.9 years; range, 2-10 years), 290 patients (320 or 95% of the THAs) completed the questionnaire. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
78
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 15 publications
2
78
1
5
Order By: Relevance
“…This may be disadvantageous especially with hard-on-hard articulations, as the impact can cause local damage of the contacting surfaces. A click and a squeak are sounds produced by some hardon-hard articulations [10][11][12]. The click is likely to result from the impact of the separated bearing surfaces after the heel strike.…”
Section: Introductionmentioning
confidence: 99%
“…This may be disadvantageous especially with hard-on-hard articulations, as the impact can cause local damage of the contacting surfaces. A click and a squeak are sounds produced by some hardon-hard articulations [10][11][12]. The click is likely to result from the impact of the separated bearing surfaces after the heel strike.…”
Section: Introductionmentioning
confidence: 99%
“…Ceramic-on-ceramic combinations have been found to squeak and break [25,39] and require optimal placement to avoid the risk of neck-to-socket impingement [41,43]. Metal-on-metal combinations have been associated with pseudotumor formation [2,21] and increased metal ion release, which may lead to cell apoptosis and to DNA changes [22].…”
Section: Introductionmentioning
confidence: 99%
“…Stanat and Capozzi [30], in a metaanalysis of 12 studies assessing outcomes after CoC THA, noted the frequency of squeaking to be 2.4%. However, studies assessing noise generation as a whole (inclusive of squeaking) have reported much higher frequency rates [23,24]. In a prospective evaluation of 208 CoC THAs, McDonnell et al [24] noted 11% to report noises other than squeaking, 8% irreproducible squeaking, and 13% reproducible squeaking.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of noise generation in hardon-hard bearings is an area of much debate, because some studies have pointed toward component design [30,31], others have reported decreased acetabular inclination and anteversion to be risk factors in CoC implants [24], whereas increased acetabular inclination has been noted as a risk factor in MoM implants [4]. Additional potential causes include loss of bearing surface lubrication [7,32] and femoral component neck geometry [23]. Our study suggests that noise generation is associated with residual symptoms after THA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation